Self-assembled chloro-bridged metallo-prismatic cations of the general formula [M6(?5-C5Me5)6(?3-tpt)2(?-Cl)6]6+ (M = Rh, Ir; tpt = 2,4,6-tri(pyridin-4-yl)-1,3,5-triazine) - Govindaswamy, Padavattan; Süss-Fink, Georg; Therrien, Bruno (My University, 2007)
Two cationic pentamethylcyclopentadienyl metal-based hexanuclear complexes with trigonal prismatic architecture were synthesized through a two-step strategy. Dinuclear [M(?5- C5Me5)(?-Cl)Cl]2 (M = Rh and Ir) react with 2,4,6-tri(pyridin-4-yl)-1,3,5-triazine (tpt) in CH2Cl2 to give trinuclear [Rh3(?5-C5Me5)3(?3-tpt)Cl6] (1) and [Ir3(?5-C5Me5)3(?3-tpt)Cl6] (2), resp. Addn. of Ag triflate to 1 and 2 in CH2Cl2 connects two identical triangular panels to form the hexanuclear metallo-prismatic cations [Rh6(?5-C5Me5)6(?3-tpt)2(?-Cl)6]6+ (3) and [Ir6(?5-C5Me5)6(?3-tpt)2(?-Cl)6]6+ (4), resp. Cations 3 and 4 were isolated as their triflate salts and characterized by 1H NMR, IR and UV/visible spectroscopy. [on SciFinder(R)]
Keywords: self assembly rhodium iridium prism chloro bridged pentamethylcyclopentadienyl